Vocational profiles and competences in nature conservation for development of sustainable society - Sajovic, Alenka; Kolnik, Karmen (Journal for Geography, 2011)
The paradigm of sustainable development steeps dynamic balance between man and nature since it requires well considered management of natural resources of our planet. To address the nature conservation problems (loss of biodiversity due to intensive agriculture, thoughtless interventions into ecosystems, introduction of alien species, etc.), is important to develop the knowledge and skills to enable understanding of nature and its processes as well as to understand legality of sociology, psychology, economy, law etc. This paper will briefly present the importance of the nature conservation for sustainable society and will give guidance to develop the key skills and professional competencies to function effectively in the field of nature conservation.
Keywords: sustainable development; nature conservation; professional profile; competencies